Sex-specific variations in patients with atrial fibrillation: a retrospective study - Direcksze, Naveen D. K. N.; Kalatsei, Liudmila V.; Cheshani Lakni, Pitadeniya Gamage; Pumesha Sathsarani Polhengoda, Polhengoda Mohottalalage (International Journal of Research in Medical Sciences, 2025)
Background: The most common and persistent arrhythmia today is atrial fibrillation (AF). There is conflicting data as to whether or not gender plays a role in the association of various risk factors and the development of AF. There are many gaps in our knowledge of the gender differences in AF and many opportunities for future research. The purpose of this study is to determine the clinical, laboratory and echocardiographic gender variations in patients with AF. Methods: This retrospective study included 90 patients with persistent and paroxysmal form of AF who were hospitalized to the Grodno Regional Cardiology Center for treatment from January to December 2024. Patients were divided into 2 groups. Group 1 consists of 44 male patients, while Group 2 consisted of 46 female patients. The following diagnostic and instrumental techniques of clinical, laboratory and transthoracic echocardiography. The exclusion criteria from the study included patients with chronic rheumatic heart disease, valvular pathology of the heart requiring surgical correction, with prosthetic heart valves, with oncological diseases and with severe concomitant extracardiac pathology. Results: Female patients with AF were older and more prone to hypertension, while both groups demonstrated high percent of comorbidities such as coronary artery disease, obesity and diabetes. Male patients had significantly lower levels of renal function parameters; and female patients had a tendency to electrolyte imbalance. Conclusions: This retrospective study illustrates the importance of sex-specific variations in patients with AF for earlier diagnosis and how to implement better interventional strategies to improve latter prognosis.